Improving coordination of data and actors for disaster-responsive housing and safer communities - Perugia, Francesca; Babb, Courtney; Scherini, Rebecca; Rowley, Steven; Logan, C.; Shirowzhan, S.; Lu, Y.; Pettit, C. (Australian Housing and Urban Research Institute Limited, 2025)
Executive summary Key points • This research project examines how key actors involved in the housing planning and delivery process in New South Wales, Victoria and Western Australia use data to assess disaster risk associated with flooding, bushfires and cyclones. • Assuming a users' perspective, the research discusses how data could be better used and shared for the planning and delivery of new housing to reduce the impact of disaster events. • Australia has a complex data landscape. It is unorganised and characterised by data fragmentation and duplication. • Flood hazard data are the most inconsistent data in terms of accuracy, data coverage, accessibility and availability. • While overall data availability and accessibility have improved over time, access to spatialised data identifying potential and actual impacts associated with natural disasters is lagging behind. • In the survey conducted as part of the research, key actors involved in housing planning and delivery identified state and local government policies as playing an essential role in disaster risk assessment, second only to hazard data. • Planning processes are not agile enough to keep up with the fast pace of information and available data. • There is a siloed approach to policy development. This limits information flow between agencies, and results in a disconnect between planning and housing policies at the strategic level. • The three priority areas to improve in decision-making processes were identified as: improved data collection and sharing practices, use of decision-supporting tools for risk assessment, and risk disclosure and communication. • Applying digital solutions to urban development will require advancement in the institutional capacity of the agencies involved in setting, managing and using these platforms.